Mathematical Communication Skills in Realistic Mathematics Education Using Algebra Tiles on Quadratic Factorization - Ikha Yuliati; Fitriyatul Qomariyah; Dimas Danar Septiadi; Fatimatuz Zahroh; Rany Widyastuti (Indonesian Journal of Mathematics and Natural Science Education, 2025)
This qualitative descriptive study aimed to explore students' mathematical communication abilities in discovering the concept of quadratic factorization through Realistic Mathematics Education (RME) using algebra tiles. Conducted at SMA Bustanul Mubtadiin Pamekasan with 24 tenth-grade students as subjects, the research focused on three aspects: the implementation of RME-based learning with algebra tiles, students’ written mathematical communication, and students’ oral mathematical communication. Data were collected through observation, tests, and interviews, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings revealed that RME facilitated students’ gradual understanding of quadratic factorization, transitioning from contextual problems to abstract concepts. Students demonstrated initial strengths in identifying known information and creating visual models in written communication but showed difficulties in explaining strategies and drawing conclusions. In contrast, students’ oral communication was more developed, especially in expressing problem-solving strategies. These results highlight RME’s effectiveness in supporting visual and procedural aspects of mathematical communication, though further reinforcement is needed to improve students’ reflective and comprehensive expression. However, this study is limited by its small sample size within a single school and its narrow focus on qudratic factorization, which may affect the generalizability of the findings.